Fruit Flies of Economic Importance XI (CRC Press, 2026)
Fruit flies (Diptera: Tephritidae) adversely impact the ability of the world’s nations to feed a growing world population. Hundreds of scientists work throughout many countries studying economically damaging fruit flies to improve our understanding of these pests and how to manage them. This book contains 19 contributions from many scientists, which is intended to improve the ability of all nations to manage tephritids and to provide good-quality food for their people. This book starts with a reflection on the career and contribution of Prof. Antigone Zacharopoulou. It continues with three chapters expanding our knowledge and information on the biology, ecology, physiology, and behavior of tephritid flies. The following three chapters explore opportunities for international trade. Aspects of the Sterile Insect Technique (SIT) and natural enemies from different countries are explained in the next five chapters. Finally, the last seven chapters describe a diverse range of action programs and area-wide Integrated Pest Management (IPM). Key features: Provides information on fruit fly diversity, courtship, and components involved in mating success. Offers opportunities to improve international trade on fruits susceptible to tephritids. Explores methods to optimize the components of the SIT and the use of parasitoids. Provides new insights into area-wide IPM and action programs. Includes contributions from relevant fruit-growing areas of the globe. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.